Effectiveness of Group Counseling using Wants, Direction, Evaluation, Planning (WDEP) Techniques to Improve Students’ Responsibility Attitude - Nindy Ayu Nurbaiti; Iis Latifah Nuryanto (Ma'soem University, 2024)
Responsibility is an inherent obligation for every individual and a necessity to accept the consequences of one's actions. Therefore, students, as members of a school community, must possess appropriate responsibility attitudes. To investigate the improvement of these attitudes, this study examined the effectiveness of the WDEP group counseling technique among 8th-grade students at SMP Negeri 2 Gamping. This research employed a quantitative methodology, utilizing a pre-experimental design, specifically a one-group pretest-posttest approach. The population consisted of all 151 8th-grade students at SMP Negeri 2 Gamping. A nonprobability sampling technique, specifically purposive sampling, was used to select a sample of 5 students. A student responsibility attitude questionnaire served as the research instrument. Data analysis was conducted using a paired t-test. The findings confirmed the hypothesis, demonstrating that the WDEP group counseling technique significantly enhanced the responsibility attitudes of the 8th-grade students. The t-test results yielded a t-value of -8.398 with a significance level (Sig.) of 0.001, which is less than 0.05. This indicates that the WDEP group counseling technique effectively improves students' responsibility attitudes at SMP Negeri 2 Gamping.